Livestock Performance in Warm‐Climate Silvopastures Using Tree Legumes. (1st September 2016) - Costa, Suellen B. de M.; de Mello, Alexandre C. L.; Dubeux, José C. B.; dos Santos, Mércia V. F.; Lira, Mario de A.; Oliveira, João T. C.; Apolinário, Valéria X. O.
Abstract : Tree legumes are a viable option to increase ecosystem services provided by warm‐climate grasslands. Benefits of using tree legumes in silvopasture systems (SPS) include the provision of shade for livestock, biological N2 fixation, and C sequestration. This study assessed cattle performance and pasture characteristics in signalgrass ( Brachiaria decumbens Stapf.) pastures in monoculture or in SPS. The following treatments were assessed: (i) signalgrass/sabiá ( Mimosa caesalpiniifolia Benth.), (ii) signalgrass/gliricidia [ Gliricidia sepium (Jacq.) Kunth ex Walp.], and (iii) signalgrass monoculture. Crossbred steers were managed under continuous stocking and variable stocking rates. Response variables included herbage mass, herbage allowance, stocking rate, average daily gain (ADG), gain per area (GPA), in vitro dry matter digestibility (IVDMD), and crude protein (CP). Total signalgrass herbage mass in monoculture (5091 kg DM ha −1 ) was greater ( P ≤ 0.05) compared with SPS (3964 kg DM ha −1 ). Green signalgrass herbage mass, however, was greater ( P ≤ 0.05) for SPS (2237 kg DM ha −1 ) compared with monoculture (1934 kg DM ha −1 ). Herbage allowance, IVDMD, CP, stocking rate, ADG, and GPA did not differ among treatments, with average values of 2.9 kg −1 green herbage mass (DM) kg −1 live weight; 633 g kg −1, 55 g kg −1, 1.9 animal units (AU) ha −1 (1 AU = 450 kg live weight); 0.57 kg −1 AU −1 d −1 ; and 30 kg ha −1 28 d −1, respectively. During the establishment phase (3 yr), SPS with tree legumes can produce as much livestock gain as signalgrass in monoculture, providing other ecosystem services and marketable products, increasing land use efficiency. Core Ideas Livestock production was similar in silvopasture systems and signalgrass monoculture. Silvopasture systems provided additional ecosystem services compared with grass monoculture. The use of tree legumes adds biologically fixed N2 and provide other ecosystem services. Trees compete with herbaceous vegetation and might reduce livestock production in the long term.